Easing into Klein: Segal, J (1992) Melanie Klein. London: Sage Publications. ISBN 0-8039-8477-4. - Ivey, Gavin (PINS-Psychology in Society, 2026)
Melanie Klein (1882-1960) has arguably influenced the direction of psychoanalysis more than any other individual after Freud. She was the first European psychoanalyst to become a member of the British Psycho-Analytical Society and, such was the impact of her work, that she soon became its dominant influence. Significantly, whereas most students and professional psychologists have a rudimentary, if distorted, understanding of Freudian psychoanalysis - gleaned mainly from glossy American texts - very few are familiar with Kleinian theory, let alone its clinical and social implications. There are a number of reasons for this.